1999
DOI: 10.1002/(sici)1521-3935(19990601)200:6<1485::aid-macp1485>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state13C NMR of microscopic order in transcrystalline films of isotactic poly(propylene)

Abstract: The microscopic orientational order in a variety of transcrystalline films of isotactic poly(propylene) was investigated by means of two‐dimensional solid‐state NMR. From the experimental results the orientation distribution function of the microcrystallites relative to the macroscopic growth direction was determined. The NMR measurements were performed at room temperature on samples that had been crystallized at conditions at which the morphology of spherulitic crystallization changes as a function of tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It can induce outstanding properties when adequately dispersed in polymeric matrix, such as rigidity increases without important losses in ductility, enhancement in electrical conductivity, nucleate crystallinity and thermal properties [8][9][10][11][12][13][14]. Unfortunately, carbon nanotubes have a trend of spontaneous aggregation because of their large surface area and high surface energy, which further limits their use [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It can induce outstanding properties when adequately dispersed in polymeric matrix, such as rigidity increases without important losses in ductility, enhancement in electrical conductivity, nucleate crystallinity and thermal properties [8][9][10][11][12][13][14]. Unfortunately, carbon nanotubes have a trend of spontaneous aggregation because of their large surface area and high surface energy, which further limits their use [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fibers, which are closely related to carbon nanotubes, can nucleate crystallinity in isotactic polypropylene. [3][4][5][6][7][8][9] This nucleating ability leads to transcrystallization, which is a region of highly oriented crystalline material with the c-axis parallel to the fiber surface at regions very close to the fiber surface. 10 This orientation is a result of very dense nucleation on the fiber, which consequently restricts crystal growth in the direction normal to the fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Use of rotor synchronized experiments demonstrated that both hard and soft segments are well oriented (155). Studies of oriented polyamide fibers (156) and of orientation in films of isotractic poly(propylene) (157) have been reported. Similar experiments have also been used to study uniaxially drawn poly(ethylene terephthalate) (158), poly(ethylene isophthalate).…”
Section: Synthetic Polymersmentioning
confidence: 99%